Nekaj nestandardnih metod za računanje determinant - Kramar, Edvard (Obzornik za matematiko in fiziko, 2012)
We present some simple nonstandard algorithms for evaluation of determinants. We are using subdeterminants of order two, removing some row and column or subtracting some number from all elements of matrix.
Keywords: determinant; determinanta; Hessenberg matrix; Hessenbergova matrika; linear algebra; linearna algebra; matrix theory; poddeterminanta; subdeterminant